‫‪SCT‬‬‫‪-‬‬‫تبسة‬ ‫‪-‬‬‫للفترة‬‫‪2013‬‬ ‫‪-‬‬‫‪2017‫أث‬‫ر ‬‫الرفع‬ ‫التشغيلي‬ ‫على‬ ‫العائد‬ ‫والمخاطرة‬ ‫دراسة‬‫حالة‬ ‫مؤسسة‬ ‫الإسمنت‬ ‬‬ - ‬‫صبرينة‫ أوذاينية ‬; ‬‫يمينة‫ كلايعية‬ (My University, 2018)
operating leverage is one of the most important decisions made by the direction of the institution to achieve its objectives: the value of the organization and the value of its profits are the two most important objectives and This is not done that thanks to a good investment which allows you to achieve satisfactory returns to satisfy all parties involved in the institution. We must not forget that every investment comes with risks potential. The objective of our study is to determine whether the decision to increase the leverage operational impact on performance and risk at the same time or not? And this thanks to a field study within the Société Cimenterie Tbessa for the period (2013-2017), Using a set of indicators and relationships, we have also adopted a statistical program from E-views7 Among the most important conclusions of our study is the existence of a relationship positive relationship between operational leverage, returns and risk, as well as the absence impact of operational leverage on returns and risks. We recommend that companies exploit their fixed assets to increase their operational capacity, and generate significant profits, given that these assets constitute a significant portion of total assets. ........................................................... تعد الرافعة التشغيلية أحد أهم القرارات التي اتخذتها اتجاه المؤسسة لتحقيق أهدافها: قيمة المنظمة و وقيمة أرباحها هما أهم هدفين وهذا لا يتم وذلك بفضل الاستثمار الجيد الذي يتيح لك تحقيق عوائد مرضية بما يرضي جميع الأطراف المشاركة في المؤسسة. يجب ألا ننسى أن كل استثمار يأتي مع المخاطر محتمل. الهدف من دراستنا هو تحديد ما إذا كان قرار زيادة الرافعة المالية تأثير العمليات على الأداء والمخاطر في نفس الوقت أم لا؟ وذلك بفضل دراسة ميدانية قامت بها شركة إسمنت تبسة ل الفترة (2013-2017)، وباستخدام مجموعة من المؤشرات والعلاقات قمنا كما اعتمدت برنامجا إحصائيا من E-views7 ومن أهم استنتاجات دراستنا هو وجود علاقة وجود علاقة إيجابية بين الرافعة التشغيلية والعوائد والمخاطر، فضلا عن الغياب تأثير الرافعة التشغيلية على العوائد والمخاطر. ونوصي الشركات باستغلال أصولها الثابتة لزيادة أصولها القدرة التشغيلية، وتحقيق أرباح كبيرة، نظرا إلى أن هذه تشكل الأصول جزءًا كبيرًا من إجمالي الأصول.